The effects of virtual business events on attitudes and behavioural intentions of Generation Z - Boros, Kitti; Keller, Krisztina (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER The virtual form of business events has grown in popularity as a result of smart technology. The MICE industry is being challenged by the emergence of a new type of consumer on the business events market: members of Generation Z, who were born in the age of digital technology and some of them are currently enrolled in undergraduate programmes at universities. The relationship between members of Generation Z studying in higher education and virtual events is determined by unique characteristics. This paper focuses on identifying virtual business event challenges from the perspective of undergraduate students, as the younger generation becomes more involved in business events. METHODOLOGY Primary research was conducted among students enrolled in undergraduate economics programmes at two Hungarian universities. Our quantitative research reveals (1) roles in which university students tend to appear at virtual and face-to-face (F2F) business events and (2) lessons drawn regarding the organisation of virtual business events from the perspective of university students. We used an online self-filled questionnaire survey with 556 valid responses. MOST IMPORTANT RESULTS The main characteristic of Generation Z is their high level of knowledge of technology and their dependence on it. The results of the research show that students attend virtual business events as participants and speakers alike and that they find such events at least as useful as F2F business events. Nevertheless, it can be seen that university students represent a business potential for event organisers. Although university students found virtual events to be slightly more efficient, they still consider F2F events important. RECOMMENDATIONS In light of these findings, managerial implications are defined so that they represent innovative technologies and can encourage Generation Z members to become more involved in business events.